ANALISIS INTERAKSI SOSIAL SISWA DI KELAS XI ILMU-ILMU SOSIAL SMA NEGERI 1 SUNGAI PINYUH - Sumarni, Ririn; Imran, Imran; Ramadhan, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this study was to find out information related to studens social interactions in Class XI of the social sciences of SMA Negeri 1 Sungai Pinyuh. With Sub problems 1. What is the pattern of students' social interaction in the form of collaboration in class XI of the social sciences of SMA Negeri 1 Sungai Pinyuh? 2. What is the process of social interaction of students in class XI of the social sciences of SMA Negeri 1 Sungai Pinyuh. The method used in this study is a qualitative method with descriptive analysis. Data collection is obtained from words and images. After the data is collected, the data is presented and a conclusion is drawn. The results were obtained that the pattern of students' social interactions that included aspects of collaboration had been going well, students had interacted well with their classmates, there were no significant conflicts or disputes. The process of social interaction of students which includes social contact and social communication has also been going well, there is no difference between each other, they respect each other, respect, and help when one of them experiences a problem or is in distress, students in class XI of Social Sciences at Sungai Pinyuh Public High School 1 no one felt difficulties when communicating with their peers. Teachers must always supervise students so that disputes or disputes occur between students. Students should also always be educated about tolerance and cooperation so that differences do not occur between students.Keywords: Interaction Pattern, Interaction Process, Students